PENGARUH PROMOSI JABATAN DAN STRES KERJA TERHADAP LOYALITAS KERJA KARYAWAN PT. MINANGA GROUP: The influence of Job Promotion and Work Stress on Employees’ Loyalty of PT. Minanga Group (Ekonomika, 2023)
This research discussed the influence of Job Promotion and Work Stress onEmployees’ Loyalty of PT. Minanga Group. The data collection technique usedinthis research was through the distribution of questionnaires. The populationwas 68 people. The data analysis technique used was Multiple Linear Regression.Based on the results of partial analysis, there was aninfluence of JobPromotionon Employees’ Loyalty of PT. Minanga Group with a t-count value of4,771. The Work Stress variable had aninfluence on the loyalty of employees ofPT.Minanga Group with a t-count value of 4,738. Simultaneously, it was foundthatthere was an influence of Job Promotion and Work Stress on Employees’Loyalty of PT. Minanga Group. The coefficient of determination (R2) obtainedwas 0.860. This meant that the contribution of the influence of Job Promotion andWork Stress on Employees’Loyalty of PT. Minanga Group was 86% while theremaining 14% was influenced by other variables outside of this research such asBonus, Work Environment, Work Facilities (Jusuf, 2021:49)